Ecotourism Development Strategy in Preserving Local Wisdom of Betawi Culture - Nurseha, Nurseha; Suswandari, Suswandari; Eko Digdoyo; Nur Fajar Absor (STKIP Taman Siswa Bima, 2024)
This research aims to describe the potential for ecotourism in the Setu Babakan Betawi Cultural Village, analyze ecotourism development strategies in preserving the local wisdom of Betawi culture, analyze the impact of ecotourism development for the community in the Setu Babakan Betawi Cultural Village, and analyze the obstacles and challenges of ecotourism development in the Betawi Cultural Village Setu Babakan. This research uses a qualitative method with a phenomenological approach. The results of the research show that the development of the Setu Babakan Betawi Cultural Village area as ecotourism is a model for preserving Betawi culture based on the available natural environment. The potential for ecotourism in the Setu Babakan Betawi Cultural Village is natural resources, agro tourism, cultural tourism, water tourism, culinary tourism, and Museum Betawi. Furthermore, the strategy for developing ecotourism in preserving local Betawi cultural wisdom is to collaborate with other parties, carry out promotions, and procure typical Betawi plants. Meanwhile, the impact for the community is to increase people's income and learn Betawi cultural values and local wisdom. The challenges faced are the independence of the area so that it does not depend on the regional government, efforts to attract visitors through various media, and ways to make Betawi culture loved by the community, while the obstacles are budget problems from the government, the perception of the Betawi community as an ethnic group that is not advanced, and that it is not easy to collaboration with other parties.